The role of brand image and brand trust through electronic word of mouth in creating parent’s interest to sending children to school - Kusuma, I Made Wijaya; Wimba, I Gusti Ayu; Wijaya, Putu Yudy (Technium Social Sciences Journal, 2022)
A good education is expected to be able to lead the community to achieve the expected success, add skills, and form a good character in individuals. The purpose of this study is to analyze the role of brand image and brand trust in creating parents' interest to sending children to Bali Public School Denpasar Elementary School through electronic word of mouth as a mediating variable. The study population was all parents of students of SD Bali Public School Denpasar with a sample used as many as 100 parents of students as respondents. The research instrument uses questionnaires as well as several other data collection methods such as observation, interviews and literature and analysis methods using descriptive analysis and inferential analysis with SEM PLS analysis. The results showed that brand image and brand trust had a positive and significant effect on electronic word of mouth. Brand image, brand trust, and electronic word of mouth have a positive and significant effect on the interest of parents of students. The implication of the research is the need to provide an understanding for parents that each school is able to provide adequate education for each of its students. Young teachers should receive training on an effective teaching system so that the skills of young teachers are improved in creating an effective teaching and learning process.